2015
DOI: 10.1093/med:psych/9780199358748.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Child Sexual Abuse

Abstract: Now welcome, the most inspiring book today from a very professional writer in the world, child sexual abuse a primer for treating children adolescents and their nonoffending parents. This is the book that many people in the world waiting for to publish. After the announced of this book, the book lovers are really curious to see how this book is actually. Are you one of them? That's very proper. You may not be regret now to seek for this book to read. This inspiring book becomes one that is very booming. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…Several trauma treatments already recognize the importance of children's meaning-making (Chaffin et al, 2004;Deblinger, Mannarino, Cohen, Runyon, & Steer, 2011;Lieberman, Van Horn, & Ippen, 2005;Valentino, Comas, Nuttall, & Thomas, 2013;Visser, Leeuwenburgh, & Lamers-Winkelman, 2007). For example, child parent psychotherapy highlights the importance of a relationship focus in the treatment of mother-child dyads after IPV exposure and helps the child and the mother in creating a joint trauma narrative .…”
Section: Discussionmentioning
confidence: 99%
“…Several trauma treatments already recognize the importance of children's meaning-making (Chaffin et al, 2004;Deblinger, Mannarino, Cohen, Runyon, & Steer, 2011;Lieberman, Van Horn, & Ippen, 2005;Valentino, Comas, Nuttall, & Thomas, 2013;Visser, Leeuwenburgh, & Lamers-Winkelman, 2007). For example, child parent psychotherapy highlights the importance of a relationship focus in the treatment of mother-child dyads after IPV exposure and helps the child and the mother in creating a joint trauma narrative .…”
Section: Discussionmentioning
confidence: 99%
“…A. Cohen, Mannarino, & Kundsen, 2005;J. A. Cohen, Mannarino, Perel, & Staron, 2007;Deblinger, Lippman, & Steer, 1996;Deblinger, Mannarino, Cohen, Runyon, & Steer, 2011;Deblinger, Stauffer, & Steer, 2001;King et al, 2000), domestic violence (J. A.…”
Section: Tf-cbtmentioning
confidence: 99%
“…So far, only two studies have investigated the sources of symptom improvement in TF-CBT. The first study was a dismantling study that aimed to understand how treatment length and the trauma narrative component were related to outcome (Deblinger et al, 2011 (Holt, Jensen, & Wentzel-Larsen, 2014). The authors found that caregivers experienced reductions in their own levels of distress during their child's treatment.…”
Section: Understanding How Treatment Leads To Changementioning
confidence: 99%
See 1 more Smart Citation
“…Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) is an evidence-based treatment for traumatized children ages 3–18 years and their non-offending parents or caregivers (Cohen et al 2006; Deblinger et al 2015; www.musc.edu/tfcbt). TF-CBT has strong empirical evidence for alleviating clinical symptoms of posttraumatic stress, depression, anxiety, externalizing behavior problems, and improving adaptive functioning, in youth with complex trauma (e.g., McMullen et al 2014; Murray et al 2015).…”
Section: Introductionmentioning
confidence: 99%